Contribution of Substorm‐Injected Electrons to the High‐Frequency Plasmaspheric Hiss Generation: A Statistical Study by Van Allen Probes - Qi Yan; Zhaoguo He; Jiang Yu; Xiangling Ding (Geophysical Research Letters)
Abstract High‐frequency plasmaspheric hiss (HFPH) is considered to be excited by substorm‐injected electrons in a case study (He et al., 2019, https://doi.org/10.1029/2018gl081578). To better understand its generation, we performed a statistical study on this wave and electron distributions, based on the Van Allen Probe data from 2012 to 2018. It shows HFPH cover a wide space from predawn to dusk side during active substorms (AE∗≥300 nT), with large amplitudes (>20 pT) at 3<L<5. Simultaneously, injected electrons are enhanced in the energy range from ∼500 eV to tens keV. Calculated linear wave growth rates driven by the injected electrons suggest HFPH is more effectively excited at dawnside, consistent with observations. Besides, the effective energy band of the electrons related to a wave decreases as L shell increases and the higher frequency wave is excited over lower L shells. Those explain HFPH spatial distributions and provide new insights into contribution of substorm‐injected electrons to HFPH generation.